Central hemodynamics and the discrepancy between central blood pressure and brachial blood pressure. Issue 40 (7th October 2022) - Park, Jin-Sun; Shin, Joon-Han; Park, Jeong-Bae; Choi, Dong-Ju; Youn, Ho-Joong; Park, Chang-Gyu; Kwan, Jun; Ahn, Youngkeun; Kim, Dong-Woon; Rim, Se-Joong; Park, Seung-Woo; Sung, Jidong; et al.
Abstract : Despite similar brachial blood pressure, central hemodynamics could be different. The objective of the present study was to investigate the factors, which could influence the discrepancy between central BP (cBP) and brachial blood pressure. Six hundred forty-seven patients (364 males, 48 ± 12 years old) were enrolled. Using applanation tonometry, cBP was noninvasively derived. The median difference between brachial systolic BP (bSBP) and central systolic BP (cSBP) was 8 mm Hg. We defined the discrepancy between bSBP and cSBP as differences >8 mm Hg. For adjustment of cBP, population was divided into 3 groups according to the cBP: group 1, <140 mm Hg of cSBP; group 2, 140 > cSBP < 160 mm Hg; group 3, =160 mm Hg of cSBP. All the central hemodynamic parameters of the patients, including augmentation pressure, augmentation index (AI), heart rate (75 bpm) adjusted augmentation index (AI@HR75), and subendocardial viability ratio, were measured. Using multivariate logistic regression analysis, we evaluated the factors which could influence the discrepancy between bSBP and cSBP. Age, gender, augmentation pressure, AI, and AI@HR75 were correlated with the discrepancy between bSBP and cSBP. AI@HR75 was significantly correlated with the discrepancy between bSBP and cSBP (β-coefficient = −0.376, P < .001 in group 1; β-coefficient = −0.297, P < .001 in group 2; and β-coefficient = −0.545, P < .001 in group 3). In groups 1 and 2, male gender was significantly correlated with the discrepancy between bSBP and cSBP (β-coefficient = −0.857, P = .035 in group 1; β-coefficient = −1.422, P = .039 in group 2). In present study, arterial stiffness might affect the discrepancy between bSBP and cSBP. Also, male gender was closely related to the discrepancy between bSBP and cSBP especially with cSBP <160 mm Hg. Not only cSBP, the discrepancy between cSBP and bSBP should be considered for understanding the central hemodynamics.